(untitled) (SAARC Journal of Agriculture, 2021)
A study on integrated pest management (IPM) practices adopted by the mango growers was carried out at Mujibnagar Upazila under Meherpur district of Bangladesh during August-September 2018 using structured questionnaire. Randomly selected 112 mango growers were used for the study. Results indicated that 75.9% of the respondents were highly adopted with IPM practices during mango cultivation. According to IPM Practices Use Index (IPUI), harvesting at right stage was ranked 1st and use of sex pheromone trap was ranked 10th as commonly used IPM tactic by the growers. The use of logistic regression model in this study was identified as the significant factor of IPM adoption, explore several factors, including contact with IPM club, IFMC and Farmers Field School (FFS) and annual income from mango cultivation. SAARC J. Agric., 19(1): 125-138 (2021)